Balloon aortic valvuloplasty in the era of transcatheter aortic valve implantation (TAVI): an opportunity to revisit a previously discouraged treatment option - Weich, Hellmuth (SA Heart Journal, 2017)
Balloon aortic valvuloplasty (BAV) was described in the 1980’s but early enthusiasm was kerbed by results indicating risk of stroke and early restenosis. It therefore fell out of favour and is only indicated as a bridge to defi nitive treatment in the majority of cases. With the advent of transcatheter aortic valve implantation (TAVI) as a new form of defi nitive treatment in high risk patients with aortic stenosis, there may be a new role for BAV.